Muraqaba-Based Cognitive Restructuring for Anxiety Reduction in Muslim University Students: A Systematic Review and Integrative Conceptual Framework - Rizal Arsjad; Muzdalifa Mamonto; Yusup Tajri; Najamuddin Petta Solong; Ratna Hestiana; Aryanti Artikasari (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
Anxiety is among the most prevalent mental health problems in university students, and Muslim students in Indonesia and Southeast Asia report consistently high distress alongside limited access to culturally congruent care. Cognitive restructuring (CR), the core technique of cognitive behavioral therapy (CBT), has strong evidence for anxiety, yet its secular framing limits its resonance for religiously committed Muslim clients. Muraqaba, a contemplative discipline in Islamic Sufism grounded in the concept of ihsan, cultivates sustained metacognitive awareness of divine presence and shows structural parallels with mindfulness-based and metacognitive therapies. No systematic review has yet mapped the convergence between Muraqaba and CR or operationalized it into a clinical protocol. This study addresses that gap through a two-phase design: a systematic review followed by the development of a conceptual framework. Following PRISMA 2020 guidance, we searched Scopus, PsycINFO, ERIC, and Google Scholar in March 2024 for literature published from January 2000, with an update search in April 2026 extending coverage through March 2026. Forty-seven peer-reviewed studies and scholarly monographs met the inclusion criteria and were analyzed through thematic synthesis. The synthesis identified four convergence domains: attentional redeployment, metacognitive monitoring, cognitive defusion, and meaning reconstruction. From these domains, we propose the Muraqaba-Based Cognitive Restructuring Framework (MBCRF), a five-stage protocol comprising Niyyah Establishment, Muraqaba Induction, Islamo-Cognitive Identification, Divine Reframing, and Muhasabah Consolidation, along with five falsifiable propositions for empirical evaluation. MBCRF differs from Traditional Islamically Integrated Psychotherapy and Islamic Acceptance and Commitment Therapy by grounding integration in explicit mechanisms rather than content substitution, and by incorporating structural safeguards against spiritual bypass. Quasi-experimental and randomized trials are needed to test its efficacy